Children suffer too: emotional suffering in children during the COVID-19 pandemic - Tognetta, Luciene Regina Paulino [UNESP]; Cuadra-Martinez, David Jorge; Queiroz, Deise Maciel de [UNESP]; Bomfim, Sanderli Aparecida Bicudo [UNESP] (Unesp-faculdade Ciencias & Letras, 2022)
This research aimed to investigate how students in the Initial Years of Ensino Fundamental feel in the pandemic context. The objectives were to identify the frequency of situations in which there are signs of emotional distress in children and to verify whether there is a significant relationship between emotional distress and sociodemographic aspects (race, gender, own cell phone). A total of 1041 children from the 4th and 5th grades of Ensino Fundamental participated in the research. The instrument used for this verification was a questionnaire, containing sociodemographic aspects (ethnic-racial origin, gender, economic profile and access to communication resources) and situations related to emotional distress. The data found show that children have shown both feelings and behaviors that indicate emotional distress (fear, anxiety, loneliness, self-mutilation) and also that there are significant differences in emotional distress scores related to gender and ethnic-racial origin.
Keywords: Pandemic; Emotional suffering; Children